The Spectacle of Care: A Netnographic Study of Performative Parenting and its Implications for Child Subjectivity on TikTok and Instagram - Kartika Ekawati (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
The rapid expansion of social media platforms such as TikTok and Instagram has transformed parenting from a private relational practice into a highly visible and publicly performed activity. The growing phenomenon of performative parenting, particularly through sharenting practices and family influencer culture, has raised concerns regarding the commodification of childhood and the construction of child subjectivity in digital environments. This study aims to examine how parenting is constructed as a performative practice on social media and to analyze its implications for children’s authentic developmental experiences. This research employs a qualitative approach using netnography as the primary methodology to analyze parenting-related content on TikTok and Instagram. The study draws on Erving Goffman’s theory of performative self-presentation, Jean Baudrillard’s concept of hyperreality, and Lev Vygotsky’s perspective on child development and social interaction. Data were collected through purposive sampling of highly engaged parenting content and analyzed using thematic analysis. The findings reveal that parenting practices on social media are increasingly shaped by performative dynamics driven by audience engagement and algorithmic visibility. Parents tend to curate idealized representations of caregiving, while children are frequently positioned as objects of emotional and aesthetic content for public consumption and digital validation. The study further demonstrates that algorithmic reinforcement and social approval mechanisms contribute to the commodification of childhood experiences and may shift parenting practices away from authentic relational interaction toward audience-oriented performance. This research contributes to the growing literature on digital parenting by reframing performative parenting as a socio-digital phenomenon shaped by platform culture, visibility economies, and algorithmic systems. The findings also highlight important ethical concerns regarding children’s agency, privacy, and developmental authenticity in the digital age